Relationship between Self-Confidence and Students' Mathematical Creative Thinking Ability - Elsa Rohmania; Iyam Maryati (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Mathematical creative thinking ability and self-confidence are two important interrelated aspects in mathematics learning. Self-confidence plays a role in encouraging students' courage to put forward ideas, try various problem-solving strategies, and persevere when facing difficulties, thus potentially supporting the development of mathematical creative thinking ability. Therefore, a study on the relationship between self-confidence and mathematical creative thinking ability is important to understand the contribution of the affective aspect to the development of students' cognitive abilities. This study used a quantitative approach with a correlational method to analyze the relationship between the two variables. The subjects were eighth-grade students of SMP Negeri 8 Garut who were selected using a purposive sampling technique. Data were collected through a self-confidence questionnaire and a mathematical creative thinking ability test in the form of descriptive questions. The questionnaire and test instruments have undergone validity and reliability tests to ensure the feasibility of measuring each research variable. Based on the results of the descriptive analysis, it is known that the majority of students have self-confidence in the medium category (54%), while mathematical creative thinking ability is in the medium category (38%). Because one of the data is not normally distributed, inferential analysis was conducted using the Spearman correlation test. The results of this test indicate a significant positive relationship between self-confidence and mathematical creative thinking ability, with a correlation coefficient of 0.464 and a significance value of 0.017 < 0.05. Thus, it can be concluded that the higher the student's self-confidence, the better the mathematical creative thinking ability they have. This shows that self-confidence contributes to mathematical creative thinking ability, although it is not the only influencing factor.